High density of cytotoxic T-lymphocytes is linked to tumoral PD-L1 expression regardless of the mismatch repair status in colorectal cancer. (2nd September 2021) - Möller, Katharina; Blessin, Niclas C.; Höflmayer, Doris; Büscheck, Franziska; Luebke, Andreas M.; Kluth, Martina; Hube-Magg, Claudia; Zalewski, Katarzyna; Hinsch, Andrea; Neipp, Michael; Mofid, Hamid; Lárusson, Hannes; et al.
Abstract: Background: Immune checkpoint-inhibitors targeting the PD-1/PD-L1 system are FDA approved in microsatellite instable (MSI) or mismatch repair deficient (dMMR) colorectal cancer (CRC). PD-L1 expression is tightly linked to features connected to immune checkpoint inhibitor response, but studies on large subsets of cancers analyzing the correlation between different status of MSI/dMMR, tumor infiltrating lymphocytes and PD-L1 expression are still lacking. Methods: More than 1800 CRC were analyzed for PD-L1 by immunohistochemistry in a tissue microarray format. Data were compared to MMR, the number of intratumoral CD8 + cytotoxic T-cells, and adverse clinico-pathological parameters. Different cutoff levels for defining PD-L1 positivity in tumor cells (1%, 5%, 10%, and 50%) yielded comparable results. Results: At a cutoff level of 5%, PD-L1 positivity was seen in 5.1% of tumors. PD-L1 was more often positive in dMMR (18.6%) than in MMR proficient (pMMR) cancers (4.1%; p  < 0.0001). The number of intratumoral CD8 + lymphocytes was strikingly higher in PD-L1 positive (939.5 ± 118.2) than in PD-L1 negative cancers (310.5 ± 24.8). A higher number of intratumoral CD8 + lymphocytes was found in dMMR CRC (PD-L1 positive: 1999.7 ± 322.0; PD-L1 negative: 398.6 ± 128.0; p  < 0.0001) compared to pMMR CRC (PD-L1 positive: 793.2 ± 124.8; PD-L1 negative: 297.2 ± 24.2; p  < 0.0001). In dMMR and pMMR CRC, PD-L1 expression in tumor cells was unrelated to tumor stage, lymph node status or lymphatic/venous invasion. PD-L1 positivity in tumor associated immune cells was seen in 47.5% of cases and was significantly linked to high numbers of tumor infiltrating CD8 +, low tumor stage, and absence of lymph node metastasis and lymphatic/venous invasion ( p  < 0.0001 each). Conclusion: The data support the previously suggested fact that PD-L1 expression in tumor cells is driven by extensive cytotoxic T-cell infiltration in highly immunogenic dMMR and pMMR CRC. Frequent and intense PD-L1 expression in tumor cells of dMMR CRC may contribute to the high response rates of dMMR CRC to immune checkpoint-inhibitors.